Cape Verde : Report on the Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2009)
This report focuses on the Observance of Standards and Codes for the Financial Action Task Force 40 (FATF) recommendations for antimoney laundering (AML) and nine special recommendations for combating the financing of terrorism (CFT) in Cape Verde. The assessment reveals that Cape Verde has taken a number of measures to establish an AML framework but is less advanced with initiatives to establish an effective CFT regime. There is scope for strengthening the framework for the criminalization of money laundering and a clear need to criminalize the financing of terrorism.